(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
A problem of solid waste became in the present day common global problem for among all countries, whether developing or developed countries, and can say no country in the world today do not suffer from this dilemma which must find appropriate solutions. The problem has reached a stage that cannot be ignored or delay, but has became a daily problem occupies the minds of ecologists, economists and politicians and occupies center stage in the lists of priorities for the countries for finding scientific and radical solutions. and transport costs constitute an important component of total costs borne by the municipal districts in the process of disposal of solid waste, so any improvement in the transport system will lead to savings in transport costs, so it will use the method of Vogel approximate model of transport for reaching to a lower cost of transport solid waste generated from areas to landfill sites.